Psychological impact among health workers in effort to facing the COVID-19 in Indonesia - Dede Nasrullah; Muhammad Natsir; Retno Twistiandayani; Lilis Rohayani; Siswanto Siswanto; Ni Made Sumartyawati; Uswatun Hasanah; Ade Herman Surya Direja (International Journal of Public Health Science (IJPHS), 2021)
The coronavirus disease (COVID-19) pandemic in Indonesia has a psychological impact among health workers who are working in hospital and caring for patients with positive COVID-19. This study aimed to examines the psychological impact among health workers in effort to facing the coronavirus pandemic (COVID-19) in Indonesia. Snowball sampling technique was employed to gather the sample in the eight islands. The health workers were responded to the depression anxiety stress scales (DASS-42) questionnaire, with the total of 644 respondents. The results of this study showed that about 65.8% of respondents experienced anxiety due to COVID-19 outbreak, There were 3.3% experienced extremely severe anxiety and 33.1% experienced mild anxiety. Whereas those experienced stress due to COVID-19 outbreak were 55%, extremely severe stress levels were 0.8% and mild stress were 34.5%. Health workers who experienced depression were 23.5%. There were 0.5% with very severe depression and mild depression was 11.2%. There is a closed correlation between anxiety (r=0.152 p=0.000), stress (r=0.086 p=0.029), and depression (r=0.111 p=0.005), to the worried of being alienated if infected coronavirus (COVID-19). The Indonesian government has to handle the anxiety, stress and depression that occurs in health workers in particular and can provide protection to medical personnel so that they do not feel alienated by those around them.